2021
DOI: 10.3390/v13081499
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Based Vaccines: Pros and Cons in the World of Animal Health

Abstract: Due to the emergence of antibiotic resistance and new and more complex diseases that affect livestock animal health and food security, the control of epidemics has become a top priority worldwide. Vaccination represents the most important and cost-effective measure to control infectious diseases in animal health, but it represents only 23% of the total global animal health market, highlighting the need to develop new vaccines. A recent strategy in animal health vaccination is the use of extracellular vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Multiple studies have elucidated the significant potential of whole malaria-derived EVs as vaccine candidates (De Sousa et al, 2022;Martin-Jaular et al, 2011;Montaner-Tarbes et al, 2021). Martin-Jaular initially demonstrated that immunization of BALB/c mice with EVs derived from the nonlethal Plasmodium yoelii 17X strain resulted in attenuated parasitemia and increased survival rates when subsequently challenged with the lethal P.y17XL strain.…”
Section: Potential Applications Of Evs In Malaria Infectionmentioning
confidence: 99%
“…Multiple studies have elucidated the significant potential of whole malaria-derived EVs as vaccine candidates (De Sousa et al, 2022;Martin-Jaular et al, 2011;Montaner-Tarbes et al, 2021). Martin-Jaular initially demonstrated that immunization of BALB/c mice with EVs derived from the nonlethal Plasmodium yoelii 17X strain resulted in attenuated parasitemia and increased survival rates when subsequently challenged with the lethal P.y17XL strain.…”
Section: Potential Applications Of Evs In Malaria Infectionmentioning
confidence: 99%
“…Exosomes released from antigen-presenting cells (APCs), dendritic cells (DCs), and immunogenically dying tumor cells should be used for vaccine development because the surface binding proteins of exosomes are derived from the plasma membrane of their cells of origin (Montaner-Tarbes et al, 2021;Santos and Almeida, 2021) and their immunoprevention ability (Kanlikilicer, 2022). Exosomes from DCs have been shown to have the ability to stimulate immune responses in cancer immunotherapy with comparable effects to parental DCs.…”
Section: High Efficient Drug Delivery Vehicles and Anticancer Vaccinesmentioning
confidence: 99%
“…There are broad opportunities for the functionalization of exosomal surfaces to increase delivery targeting, and various methods for modification of RNA cargo also exist. These features make exosomes a highly promising carrier for the delivery of both therapeutic RNAs [ 106 ] and prophylactic RNA vaccines [ 107 , 108 ], although extensive further research is necessary on the donor cell selection, exosome safety, optimization and scaling-up of purification protocols, before exosome-based drug delivery is implemented into clinics.…”
Section: Why Exosomes Are Advantageous For Therapeutic Rna Deliverymentioning
confidence: 99%